Preparation for bariatric surgery for patients with morbid obesity - Sierżantowicz, Regina; Hady, Hady; Kirpsza, Bożena; Trochimowicz, Lech; Dadan, Jacek (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2012)
Obesity is a major medical, social and economic issue. Between 2000 and 2005, the number of obese patients with BMI  30 tripled and with BMI  40 – doubled. Increase in the number of co-morbidities is also observed. Researches indicate that in the group of obese patients, average life expectancy significantly decreases especially in young patients with co-existing cardio-vascular diseases. The American Gastroenterological Association (AGA) and European Association for Endoscopic Surgery (EAES) confirm that surgery is the most efficient treatment for the permanent decrease in body mass, recovery of co-morbidities and improving the quality of life. In bariatric surgery the following are used: restrictive methods which reduce volume of food intake, malabsorptive methods which limit absorption from the gastrointestinal tract and restrictive-malabsorptive methods which combine two methods mentioned above and other. The process of preparation for the surgery should take at least three months. The first phase is performed in an out-patient clinic. It is necessary to determine the blood group and examine liver, kidneys, pancreas and thyroid functions. Patients are admitted to the Surgery Department 1 day before the operation.